Canadian Pentecostals, the Trinity, and contemporary worship music : the things we sing - Tapper, Michael A. (Global Pentecostal and Charismatic Studies, 2017)
This volume offers a landmark analysis of the trinitarian impulses in contemporary worship music used by the Pentecostal Assemblies of Canada (PAOC). It considers whether the lyrics from the most commonly used PAOC songs are consistent with this Evangelical group's trinitarian statement of faith. Colin Gunton's trinitarian theology provides the theological rationale for eight original and qualitative content analyses of these songs. Three major areas are considered-the doctrine of God, human personhood, and cosmology. Making use of Gunton's notions of relationality, particularity, and perichoresis, along with several key Pentecostal scholars, this book serves as a helpful descriptive and prescriptive theological resource for the dynamic practice of a trinitarian faith.